2022
DOI: 10.1021/acsptsci.2c00120
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Swertiamarin in a Rotenone Model of Parkinson’s Disease: Role of Neuroinflammation and Alpha-Synuclein Accumulation

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disease with no permanent cure affecting around 1% of the population over 65. There is an urgency to search for a disease-modifying agent with fewer untoward effects. PD pathology involves the accumulation of toxic alpha-synuclein (α-syn) and neuronal inflammation leading to the degeneration of dopaminergic (DAergic) neurons. Swertiamarin (SWE), a well-studied natural product, possesses a strong anti-inflammatory effect. It is a secoiridoid glycoside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Furthermore, the accumulation of alpha-synuclein (α-Syn) is the major hallmark of PD. , According to previous findings, the entrance of SARS-CoV-2 into the CNS may upregulate this protein, causing aggregation. On the contrary, few studies have indicated α-Syn’s protective effect in blocking viral entry and propagation into the CNS .…”
Section: Covid-19 and Comorbiditiesmentioning
confidence: 98%
“…Furthermore, the accumulation of alpha-synuclein (α-Syn) is the major hallmark of PD. , According to previous findings, the entrance of SARS-CoV-2 into the CNS may upregulate this protein, causing aggregation. On the contrary, few studies have indicated α-Syn’s protective effect in blocking viral entry and propagation into the CNS .…”
Section: Covid-19 and Comorbiditiesmentioning
confidence: 98%
“…The metabolite alleviated the rotenone-induced α-syn overexpression in the substantia nigra (SN) and striatum. The compound showed a reversal effect on the α-syn accumulation in the 6-hydroxydopamine-induced Caenorhabditis elegans model of PD (Sharma et al, 2022). The neuroprotective effect in the intrastriatal rotenone mouse PD model was reported and a suppression of microglial and astroglial activation in SN was exhibited after administration of this secoiridoid glycoside in a rotenone mouse model (Abdel-Salam et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al . [ 32 ] has reported that just the enhanced activity of the antioxidant enzymes is not enough to control the impending damage in many conditions of oxidative stress. The observation made in the present study does corroborate with the results published by Saravanan et al .…”
Section: Discussionmentioning
confidence: 99%
“…In elderly rats, glial cell activation is more severe. A widespread increase in astrocytes and microglia is caused by unilateral rotenone infusion into the medial forebrain bundle, excluding the SN [ 32 ]. The microglial activation was observed in ROT intoxicated brains of the rat and the number of activated microglia ( Figure 5 ) were increasing with dose duration and age.…”
Section: Discussionmentioning
confidence: 99%